Satellite quantum communication via the alphasat laser communication terminal quantum signals from 36 thousand kilometers above earth - Elser, Dominique Alexander; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Marquardt, Christoph; Leuchs, Gerd; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (2015 IEEE International Conference on Space Optical Systems and Applications, ICSOS 2015, 2016)
By harnessing quantum effects, we nowadays can use encryption that is in principle proven to withstand any conceivable attack. These fascinating quantum features have been implemented in metropolitan quantum networks around the world. In order to interconnect such networks over long distances, optical satellite communication is the method of choice. Standard telecommunication components allow one to efficiently implement quantum communication by measuring field quadratures (continuous variables). This opens the possibility to adapt our Laser Communication Terminals (LCTs) to quantum key distribution (QKD). First satellite measurement campaigns are currently validating our approach.
CRIS-Team Scopus Importer:2021-06-29
Keywords: free-space optical communication; quantum cryptography; quantum key distribution; satellite quantum communication; satellite-ground laser communication